PENINGKATAN KUALITAS HIDUP LANSIA DENGAN TERAPI KEBAHAGIAAN - Kuslina, Boedi Hartadi; Magdalena, Nonie; Munthe , Rusli Ginting; Widjaja , Jahja Hamdani; Susan , Marcellia; Tjahyadi , Rully Arlan; Veronica , M. Sienly; Kristiawan , Allen (Jurnal Abdimas Bina Bangsa, 2025)
As they get older, most elderly people experience a decline in their quality of life in consequenses of old age and are often seen as a burden on their family or the environment around them. This community service activity intends to help develop the elderly not depend on other people, make themselves and the people around them happy. This service method is to provide solutions for the community (service learning), especially the elderly, with happiness therapy. The results of this service indicate that happiness therapy can change the mental condition of the elderly for the better, namely that the elderly can sleep more comfortably, manage stress, overcome daily problems, feel happy and not feel deeply sad, have self-confidence, and consider themselves valuable.